(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
A total of ten selected strains of Salmonella species, five from the environment of poultry farm and five from patients were included in this study. All strains were isolated and identified by using selective media, standard biochemical and serological tests. Antimicrobial susceptibility tests were performed by disc diffusion method using twelve commercial antibiotic discs of aztreonam, ceftriaxone, kanamycin, ciprofloxacin, gentamycin, chloramphenicol, ampicillin, erythromycin, cephalexin, tetracycline, cotrimoxazole and nalidixic acid. Plasmid profile and integron gene detection were conducted by Kado-Liu method and PCR, respectively. Only aztreonam, ceftriaxone, kanamycin and gentamycin were shown to be inhibitory to all strains. However, ciprofloxacin, chloramphenicol, amoxicilin, erythromycin, cephalexin, tetracycline, cotrimoxazole and nalidixic acid revealed different degrees of resistance pattern against environmental and clinical strains. Analysis of plasmid demonstrated that three environmental strains contained both plasmids of 140 Mda and 62 Mda. On the other hand, another three strains, one environmental and two clinical isolate only contained 140 Mda plasmid. All the plasmid containing strains (140 Mda and 62 Mda) exhibited same type of drug resistance pattern, whereas strains containing the 140 Mda plasmid only did not show similar type of resistance pattern. Therefore, no correlation was found between plasmid containing strains and drug resistance. Four environmental strains were also found to be positive for the class I integron and one clinical isolated was positive for class I integron gene conferring resistance to common antibiotics. However, none of the strains were found to contain class II integron. Therefore, the present study demonstrated that both environmental and clinical strains contain both large to middle size plasmids and integron I but not integron II. The plasmid and integron I containing strains experienced resistance to different antibiotics, used in the experiments. Dhaka Univ. J. Pharm. Sci. 15(2): 209-214, 2016 (December)